LPS differentially affects expression of CD14 and CCR2 in monocyte subsets of Post-STEMI patients with hyperglycemia. (September 2022) - Blanks, Anson M.; Pedersen, Lauren N.; Caslin, Heather L.; Mihalick, Virginia L.; Via, Jeremy; Canada, Justin M.; Van Tassell, Benjamin; Carbone, Salvatore; Abbate, Antonio; Lee Franco, R.
Highlights: Post-infarction intermediate monocyte CD14 is lower in impaired random glucose compared to normal post-STEMI patients. Lipopolysaccharide decreases classical and intermediate monocyte CCR2 and CD14, post-infarction. Impaired random glucose reduces lipopolysaccharide induced classical subset CCR2. Non-classical CCR2 correlates with serum glucose following lipopolysaccharide activation. Abstract: Aims: Following ST-segment elevation myocardial infarction (STEMI), recruitment and activation of monocytes [classical (CD14 ++ CD16 - CCR2 ++ ), intermediate (CD14 ++ CD16 + CCR2 + ), non-classical (CD14 Low CD16 ++ CCR2 Low )] are needed for myocardial wound healing. Monocyte surface receptor CC chemokine receptor type 2 (CCR2) is responsible for monocyte chemotaxis to sites of inflammation and the lipopolysaccharide (LPS)-binding protein co-receptor, CD14, is involved in pro-inflammatory monocyte activation. The purpose of this investigation was to determine the effects of ex-vivo LPS activation on monocyte subset CD14 and CCR2 expression in post-STEMI individuals with normal and elevated random blood glucose. Methods: Post-STEMI subjects were identified as normal random glucose (NG, <98 mg/dL, n = 13) or impaired random glucose (IG, ≥98 mg/dL, n = 26) and monocytes were analyzed for non-activated and LPS-activated (1 µg/mL for 4 h) CCR2 and CD14 expression. Results: Non-activated intermediate monocytes from IG showed decreased CD14 expression when compared to NG, which was maintained following LPS-activation. The NG group showed a larger absolute reduction in classical CCR2 expression, leading to a significant difference between NG and IG following LPS-activation. Conclusion: Results suggest a heightened response to pro-inflammatory activation in IG following STEMI, which may impair or delay post-STEMI myocardial healing, and thus increase the incidence of chronic heart failure. NIH 1R34HL121402.